RELATION BETWEEN LEVELS OF ANXIETY, STRESS AND REACTION TIME OF FOOTBALL PLAYERS (Fiep Bulletin - online, 2015)
The reaction time (RT) performance depends on the adequate individual level of activation.  Individual characteristics as levels of stress and anxiety can modify the brain activation and compromise the capacity of attention and the information processing of determined stimuli.  Thus, this study aimed to investigate the relation between the levels of Anxiety, Stress and RT of Feminine Amateur football players.  The sample was composed by 21 players, with mean age of 21 years.  The RT was measured by means of the software "Time of reply of a motor action" (ANDRADE and JARDIM, 2003).  The Stress was measured by means of the Perceived Stress Scale of Cohen et al. (1983) adapted by Ururahy (1997) inside the questionnaire developed by Andrade (2001).  The levels of trait and state anxiety were measured by means of the State and Trait Anxiety Inventory (STAI - Portuguese version) developed by Spielberger et al. (1979).  The data had been treated by means of descriptive statistics (frequency, percentage, mean and standard deviation) and by inference (test t).  The results had indicated that the players who had showed medium levels anxiety and stress had presented the better RTs than the players who had presented lower anxiety and stress levels.  Although the results have not presented statistics significance, this study indicates that the RT depends on a balance in the anxiety and stress levels.
Keywords: reaction time; anxiety; stress.